تطوير مادّة المحادثة القائم على الإطار المرجعي الأوروبي المشترك للغات للمبتدئين بمعهد الكافّة الإسلامي تانجيرانج - Ataska, Sabrina Salsabilla; Royani, Ahmad; Alawiyah, N Lalah (Al-Muyassar: Journal of Arabic Education, 2025)
AbstractThe use of appropriate teaching materials is crucial for creating an effective learning experience, supporting the achievement of educational objectives. One of the issues identified in teaching conversation at the Al-Kaffah Islamic Institute is that the teaching materials provided are not tailored to the students' proficiency levels. The materials used are based on personal efforts rather than being aligned with any reference framework. Therefore, this study aims to measure the effectiveness of structured teaching materials for teaching conversation at the beginner level (A1), based on the Common European Framework of Reference for Languages (CEFR). This research employed a research and development (R&D) method using the ADDIE model, which includes five phases. The researcher utilized a mixed-methods approach combining qualitative and quantitative methodologies. To collect data, the researcher relied on observations, interviews, questionnaires, and tests.This study resulted in the development of a conversation teaching material product titled “Al-Muhadathah Al-Arabiyyah” (Arabic Conversation) based on the CEFR framework for the A1 beginner level. The material includes vocabulary and exercises, expressions, dialogues, and related exercises.The effectiveness of this teaching material was validated through expert evaluations, where the material received substantial ratings ranging between 81% and 100%, categorized as "Excellent," with an average score of 95.45%. Additionally, the findings showed that the average speaking ability of seventh-grade students (Class 7A) after using the “Al-Muhadathah Al-Arabiyyah” material was 84.11%, significantly higher than their average ability before using the material, which was 51.01%. The difference between the two averages was 33.10%. This indicates that the “Al-Muhadathah Al-Arabiyyah” teaching material can effectively be used by learners at the A1 level, particularly at the Al-Kaffah Islamic Institute in Tangerang.Keywords: material development, conversation, CEFR مستخلص البحثيعد استخدام المواد التعليمية المناسبة أمرًا مهما لخلق تجربة تعليمية فعّالة مما يدعم تحقيق الأهداف التربوية. ومن المشكلات التي تم اكتشافها في تعليم المحادثة في معهد الكافة الإسلامي هو لا يتم تقديم المواد التعليمية بما يتناسب مع مستويات الطلاب، وتعتمد المواد التعليمية المستخدمة على الاجتهادات الشخصية بدلاً من الاستناد إلى أي إطار مرجعي .لذلك، تهدف هذه الدراسة إلى قياس فعالية المواد التعليمية المنظمة في تعليم المحادثة للمستوى المبتدئ A1 بناءً على الإطار المرجعي الأوروبي المشترك للغات .(CEFR) اعتمد البحث على منهج البحث والتطوير باستخدام نموذج ADDIE، الذي يشمل خمس مراحل. استخدمت الباحثة منهجاً مختلطاً يجمع بين المدخل النوعي والمدخل الكمي. ولجمع البيانات، اعتمدت الباحثة على الملاحظة، والمقابلات، والاستبيانات، والاختبارات. أدى هذا البحث إلى إنتاج منتج مادة المحادثة بموضوع "المحادثة العربية" القائم على الإطار المرجعي الأوروبي المشترك للغات CEFR للمستوى المبتدئ A1، وتتضمن على المفردات وتدريباتها،  الأساليب، ثم الحوار والتدريبات عليها. وتم إثبات فعالية هذه المادة التعليمية من خلال نتائج التحقق من قبل المحكمين، حيث حصلت المادة على تقييم جوهري بنسبة تتراوح بين (٨١٪ - ١٠٠٪) ضمن فئة "ممتاز"، وبمتوسط درجات ٩٥،٤٥٪. كما أظهرت النتائج أن متوسط قدرة طلاب الصف السابع (٧أ) على المحادثة بعد استخدام المادة التعليمية "المحادثة العربية" وهي ٨٤،١١٪ أعلى من متواسط قدرتهم قبل استخدام تلك المادة ٥١،١٪. والفرق بينهما ٣٣،١٠٪. وهذا يدل على أن مادة "المحادثة العربية" يمكن استخدامها من قبل المتعلمين في المستوىA1، خاصة في معهد الكافة للتربية الإسلامية تانجيرانج.النقاط الحاكمة : تطوير مادة، محادثة، الإطار المرجعي الأوروبي المشترك للغات.